Comparison of ARDL Model and NARDL Model: A standard Study by application on The Factors Affecting the Rate of Sudanese Economic Growth for the period (1990-2020) - Ahmed, Imtithal Mergny Mohammed; Abdelateef, Afra Hashim (Arab Journal for Sciences and Research Publishing, 2022)
This study aims to choose which model is the best the a and NARDL models to analyzing and measuring the relationship between exports, imports and remittances of Sudanese working abroad on the rate of economic growth in sudan during the period (1990-2020).The study concluded that the partial significance of the ARDL model and the strength of the estimate were better than the NARDL model. As for the effect size and its significance between the independent variable, the results were consistent between the two models.
Keywords: exports; imports; remittances of Sudanese working abroad and rate of economic growth; ardl; nardl